Primary tracheal microcystic reticular schwannoma – Case report of a rare neurogenic tumor treated by segmental tracheal resection. (February 2021) - Esch, Matthias; Teschner, Martin
Highlights: Knowledge about tracheal tumors is important to avoid misdiagnosis. Awareness of the option of tracheal resection is necessary to avoid suboptimal treatment recommendations. Microcystic reticular schwannoma is a rare variant of a neurogenic tumor and may occur in the trachea. Complete resection should be considered even without clear preoperative tumor histology. Tracheal segmental resection is a safe procedure and treatment of choice for resectable, intra-/transmural tumors causing tracheal obstruction. Abstract: Introduction and importance: Diagnosis and treatment of rare diseases are challenging because experience and evidence are limited. Primary tracheal tumors have a low prevalence but awareness of these is important to avoid misdiagnoses. We present a first case of a tracheal microcystic reticular schwannoma in which diagnosis and treatment recommendations were revised several times resulting in months of anxious uncertainty for the patient before complete resection and extensive histopathologic examination were performed. Case presentation: A 65-year old woman complained about coughing and cervical pain. Tomographies revealed a tumor of the dorsolateral trachea. After repeated biopsies pathologists and tumorboards in different hospitals could not agree on diagnosis or treatment recommendation, so the impatient patient opted for a complete resection for definite treatment. Clinical discussion: Neoplasms of the posterior mediastinum are mainly neurogenic. In rare cases they may originate in the trachea and can be difficult to differentiate from other tumor entities if only biopsies are available. Although the preoperative diagnosis was unclear, tracheal resection was performed successfully. The differential diagnoses of soft tissue sarcoma or myoepithelioma were discarded and a benign, microcystic, reticular schwannoma was confirmed by international reference pathologists. Conclusion: Microcystic, reticular schwannoma is a rare variant and may occur in the trachea. Diagnosis of such rare neoplasms can be difficult, resulting in delayed or suboptimal treatment. Often biopsies are not sufficient to reach a definite diagnosis. But even without preoperative histology, tracheal resection is a safe and feasible option for definitive treatment with very low recurrence rates.